Advancing a sociology of ignorance in the study of racism and racial non‐knowing. Issue 8 (18th July 2018) - Mueller, Jennifer C.
Abstract: By a wealth of indicators, ignorance appears a bona fide if often vexing social fact. Ignorance is socially constructed, negotiated, and pervasive; ignorance is often socially inevitable, even necessary; and, without a doubt, ignorance is socially consequential. Yet, despite its significance, ignorance has appeared a largely secondary concern among sociologists. Perhaps more perplexing, while sociologists of racism, power, and domination have long focused on the ways racial ideologies distort and mystify racial understanding to sustain White supremacy over time, we have done less to elaborate ignorance than is possible and warranted. Here, I join growing calls for a fully‐fledged "sociology of ignorance" and argue that antiracist and decolonial scholars have much to gain from and contribute to such an endeavor. This article traces the historical forebears of a "sociology of ignorance" and explores ignorance as a social concept before turning to examine precedents and increasing attention to ignorance scholarship on racism, racial domination, and racialized non‐knowing. Drawing from this work, I urge race‐critical scholars take advantage of our unique position to advance theory and methodology surrounding ignorance and the social‐cultural production of non‐knowledge as a broader area of social inquiry.